Integrated Transcriptomics and Metabolomics Reveal Key Genes and Metabolic Pathway in Flower and Fruit Color Formation of Cerasus humilis (Bge.) Sok - Shuai Zhang; Tianyuan Li; Shan Liu; Xinliang Qi; Yu Yang; Jiancheng Zhang; Luting Jia; Pengfei Wang; Xiaopeng Mu (Plants)
Anthocyanins play a pivotal role in determining the color diversity in the flowers and fruits of Cerasus humilis (Bge.) Sok. This study performed a metabolomic analysis of the flowers and fruits of two varieties differing in pigmentation phenotypes (‘Jinou 1’ and ‘Nongda 5’), and the results indicated that the cyanidin, pelargonidin, paeonidin, and delphinidin were the main substances serving as the primary pigments contributing to their striking chromatic divergence between two varieties. Transcriptome profiling revealed that several key structural genes (ChCHS1, ChDFR, ChF3H, and ChF3’H) in the anthocyanin biosynthesis pathway exhibited significantly elevated expression levels in ’Jinou 1’ compared to ’Nongda 5’. Further metabolomic and transcriptomic correlation analyses identified that ChMYB9 and ChMYB12 exhibited strong positive associations with anthocyanin pathway metabolites in both floral and fruit tissues. Notably, ChMYB9 displayed the strongest correlation with the metabolite profiles, suggesting it may serve as a core regulatory component of the anthocyanin biosynthesis. This research provides new insights into the regulatory mechanisms of anthocyanin biosynthesis in C. humilis.